Surgical management of a free-floating thrombus in the ascending aorta. (March 2019) - Campanile, Alfonso; Sardone, Mariagrazia; Pasquino, Stefano; Cagini, Angelo; Di Manici, Gino; Cavallini, Claudio
The ascending aorta is an uncommon site of noninfective thrombus. We describe the case of a 63-year-old woman who was admitted to our department with acute myocardial infarction. Coronary angiography showed occlusion of a small diagonal vessel, likely related to a distal embolization event. A transthoracic echocardiogram revealed a free-floating mass in the proximal ascending aorta. Two-and 3-dimensional transesophageal echocardiography studies were performed, and after a multidisciplinary heart team discussion, surgical removal of the mass was planned and successfully performed through a median sternotomy on cardiopulmonary bypass.